DEDICATED CNC MILLING STRATEGIES FOR COMPLEX SURFACES - Adrian BUT; Cristian POPESCU; Lucian GAL (Fiabilitate şi Durabilitate)
The parts for the aerospace sector are complex, varied models, with above average hardness, heat treated, resistant to humidity and variable stress. Comparison the “old planes “with the “new planes”, we saw the dramatically reducing the aluminium components and was replace with more components from titanium. This mean that we have high cutting temperature in manufacturing area, high stress close to the edge, tendency to deflection of the cutting tools, adhesion, and welding materials on the cutting edge. To control all these negative influences, we need dedicated cutting tools, with high cutting parameters and innovative milling strategies. The paper presents applications and processing solutions of some components from the aerospace sector, with advanced processing strategies, with the advantages and specific cases analysed.